miR-192 Mediates TGF-β/Smad3-Driven Renal Fibrosis - Chung, Arthur C.K. (American Society of Nephrology, 2010)
TGF-β/Smad3 promotes renal fibrosis, but the mechanisms that regulate profibrotic genes remain unclear. We hypothesized that miR-192, a microRNA expressed in the kidney may mediate renal fibrosis in a Smad3-dependent manner. Microarray and real-time PCR demonstrated a tight association between upregulation of miR-192 in the fibrotic kidney and activation of TGF-β/Smad signaling. Deletion of Smad7 promoted miR-192 expression and enhanced Smad signaling and fibrosis in obstructive kidney disease. In contrast, overexpression of Smad7 to block TGF-β/Smad signaling inhibited miR-192 expression and renal fibrosis in the rat 5/6 nephrectomy model; in vitro, overexpression of Smad7 in tubular epithelial cells abolished TGF-β1–induced miR-192 expression. Furthermore, Smad3 but not Smad2 mediated TGF-β1–induced miR-192 expression by binding to the miR-192 promoter. Last, overexpression of a miR-192 mimic promoted and addition of a miR-192 inhibitor blocked TGF-β1–induced collagen matrix expression. Taken together, miR-192 may be a critical downstream mediator of TGF-β/Smad3 signaling in the development of renal fibrosis.